(untitled) (MAUSAM, 1950)
The paper presents an account of some magnetic disturbances associated with solar flares and radio fade out during the period 1937-1946. The ionospheric irregularities associated with four great magnetic storms recorded at the magnetic Observatory Alibag (Bombay) are discussed. On some occasions in intense solar flare is followed about a day later by a great magnetic storm, This occurs far more often than by chance. The presence of a , Crochet " in the magnetic records occurring simultaneously with a radio fade out and the appearance of a solar eruption or flare has been interpreted as showing that radiation from the flare traveling with the speed of light causes the " Crochet", while the magnetic storm which appears between 18 and 30 hours later is attributed to corpuscular radiation traveling at a speed of 1,000 to 2,000 miles/sec. A list of sudden ionospheric disturbances or the Dellinger type from observations made in India during the period 1937-1946 has been collected and the principal features of the observations discussed.